Sustainable Framework Model (Sustia Fwm) for Traffic Impact Assessment in Malaysia - Sharifah, Awang; Nurmunira, Muhammad; A., Zulkiple; N. W., Kamruzaman; M. A., Seman; Nur Azzimah, Zamri; N., Rahman; M. R., Siti Norsita

(untitled)
Transportation plays vital role in our daily mobilization and more than 30% of our income is consumed to meet its needs and Government of Malaysia had spent more than RM 100 billion for the provision of transportation infrastructure and facilities. The proposed study emphasized on integrating existing database with homemade transportation analysis system that had been developed based on green technology approach called SusTIA-FWM. Bottlenecks in traffic impact assessment studies such as data collection and simulation were tackled since data and the results of the previous study stored in the caretaker system were recycled. A SMART Partnership study with Kuantan Municipal Council was done successfully and this framework model was recognized, so for the next study only limited data were collected to facilitate data redundancy and dependency on imported software will not being a decisive factor of a reliable traffic study anymore